The role of chemical canopy sprays and irrigation methods on the incidence of the perennial canker, Cytospora plurivora in western Colorado peach orchards - Wright, Sean, author; Stewart, Jane E., advisor; Charkowski, Amy, committee member; Uchanski, Mark, committee member (Colorado State University. Libraries, 2022)
Cytospora plurivora is a secondary pathogen that has reached near epidemic levels in peach orchards on the western slope of Colorado. C. plurivora is responsible for Cytospora canker disease and is a limiting factor in peach production in the Grand Valley. Peach growers have limited management methods available to combat this disease, which prompted an investigation into irrigation practices as well as prophylactic chemical sprays following freeze events. In late 2020, the western slope received a freeze event that caused severe damage to peach shoots, buds, and twigs. Freeze damage provides infection courts within tree tissues that C. plurivora can infect. This freeze event prompted growers to apply prophylactic chemical sprays of Captan, lime sulfur, and lime sulfur with the addition of NuFilm. An efficacy threshold of three-months post chemical spray was determined for both Captan and lime sulfur treatments. Lime sulfur with the addition of NuFilm showed a loss of efficacy at two-months post spray. Additionally, an investigation into the movement of C. plurivora conidia under differing irrigation techniques was conducted. Both drip and micro-sprinkler treatments had positive detections for C. plurivora over the course of the study. In these studies, conidia traveled much greater distances than previously shown, traveling up to 135m from the closest canker. Understanding how chemical canopy sprays and different watering practices affect the incidence of Cytospora canker disease will assist in preserving the peach industry on the western slope of Colorado.
Keywords: chemical efficacy; irrigation; plant pathology; Cytospora; canopy spray; peach